ROS-induced oxidative stress in plant cryopreservation: occurrence and alleviation - Li Ren; Min-Rui Wang; Qiao-Chun Wang (Planta, 2021)
Main conclusion Reactive oxygen species (ROS)-induced oxidative stress results in low success or even total failure of cryopreservation. Better understanding of how the plant establishes resistance/tolerance to ROS-induced oxidative stress facilitates developments of robust cryopreservation procedures. Abstract Cryopreservation provides a safe and efficient strategy for long-term preservation of plant genetic resources. ROS-induced oxidative stress caused damage to cells and reduced the ability of the plant to survive following cryopreservation, eventually resulting in low success or even total failure. This paper provides updated and comprehensive information obtained in the past decade, including the following: (1) ROS generations and adaptive responses of antioxidant systems during cryopreservation; (2) expressions of oxidative stress-associated genes and proteins during cryopreservation; (3) ROS-triggered programmed cell death (PCD) during cryopreservation; and (4) exogenous applications of enzymatic and non-enzymatic antioxidants in improving success of cryopreservation. Prospects for further studies are proposed. The goal of the present study was to facilitate better understanding of the mechanisms by which the plant establishes resistance/tolerance to oxidative stress during cryopreservation and promote further studies toward the developments of robust cryopreservation procedures and wider application of plant cryobiotechnology.